Prevalence of Minimum Meal Frequency Practice and Its Associated Factors among Children Aged 6 to 23 Months in Ethiopia: A Systematic Review and Meta-analysis - Addisu Dabi Wake (SAGE Publishing, 2021)
Background . Inappropriate complementary feeding practices are amongst the key causes of child undernutrition. It rises the risk of undernutrition, illness, and mortality among children. Objectives . This study was aimed to determine the pooled prevalence of MMF practice and associated factors among children aged 6 to 23 months in Ethiopia. Methods . The search was conducted by using the following electronic databases; PubMed/MEDLINE, HINARI, EMBASE, Google Scholar, Web of Science, Scopus, African journals, and Google for grey literature. The publication bias was determined by using a funnel plot and Egger's test. The heterogeneity between the studies was checked by using I 2 statistic. The subgroup analysis was done by sample size, region, and year of publication. Result . A total of 20 studies with 12 656 study participants were included in the present systematic review and meta-analysis. The pooled prevalence of MMF practice among children aged 6 to 23 months in Ethiopia was estimated to be 63.80% (95%CI: 56.59, 71.01). PNC visit (AOR = 1.90, 95%CI [1.31, 2.49]), wealth index (AOR = 2.11, 95%CI [1.42, 2.81]) and age of child (AOR = 5.75, 95%CI [4.25, 7.26]) were factors significantly associated with MMF among children aged 6 to 23 months. Conclusion . The findings showed that the pooled prevalence of MMF among children aged 6 to 23 months in Ethiopia was relatively low. PNC visit, wealth index and age of child were factors significantly associated with MMF among children aged 6 to 23 months. Therefore, community-based health education concerning the recommended MMF among children aged 6 to 23 months is required to take place.